2017
DOI: 10.1186/s13643-016-0402-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and materno-fetal outcomes related to cesarean section delivery in private and public hospitals in low- and middle-income countries: a systematic review and meta-analysis protocol

Abstract: BackgroundDespite the well-established morbidity, mortality, long-term effects, and unnecessary extra-cost burden associated with cesarean section delivery (CSD) worldwide, its rate has grown exponentially. This has become a great topical challenge for the international healthcare community and individual countries. Estimated at three times the acceptable rate as defined by the World Health Organization in 1985, the continued upward trend has been fuelled by higher income countries. Some low- and middle-income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
1
16
0
1
Order By: Relevance
“…This review is shaped from the published protocol [32], which was registered within the International…”
Section: Methodsmentioning
confidence: 99%
“…This review is shaped from the published protocol [32], which was registered within the International…”
Section: Methodsmentioning
confidence: 99%
“…In the last decades, an invariable upward trend has been evident mainly in low-and middle-income countries. China (64.1%), Colombia (46.4%), Dominican Republic (56.4%), Egypt (51.8%), Iran (47.9%), and Brazil (55.6%, 80% for second deliveries) -when the first was by cesarean, are some examples [7,11,15].…”
Section: : 319% (Low-risk Patients: 269%)mentioning
confidence: 99%
“…Several systematic reviews have shown that, although CS can be a truly life-saving procedure in some cases, it's also associated with anomalous short-term immune response in the newborn, and a greater risk of developing immune-mediated diseases such as asthma, allergies, or DM type 1. From a financial perspective, globally, the cost of practicing CS without a clear medical indication has been estimated at $2.32 billion [15,16].…”
mentioning
confidence: 99%
“…The CD rate increase persists despite established consequences including morbidity, mortality, long‐term effects, and unnecessary costs of non‐medically indicated CDs. Moreover, there is evidence that higher rates of CDs are not associated with improved maternal or fetal outcomes …”
Section: Introductionmentioning
confidence: 99%
“…The upward trend in CDs, once led by some high‐income countries, is now being surpassed by low‐ and middle‐income countries . For example, Colombia, a middle‐income country, has experienced an increase in CDs in the past two decades .…”
Section: Introductionmentioning
confidence: 99%